The ideal prophet - Kamal-ud-din, Khwaja ([S.l.] : Ahmadiyya Anjuman Ishaat Islam Lahore USA, 2011)
First published in 1925 from the Woking Muslim Mission in England, this book presents the noble character and high moral qualities of the Holy Prophet Muhammad, showing him to be the Ideal Prophet in every sense.
Kindle eBook.